Zeolite Catalyzed Aldol Condensation Reactions - Inegbenebor, Adedayo I.; Mordi, Raphael C.; Ogunwole, Oluwakayode M. (International Journal of Applied Sciences and Biotechnology, 2015)
The review is based on the description of zeolite structure, uses, synthesis, and catalytic aldol reaction in aldol condensation. An internal aldolcondensation reaction has been achieved over ZSM-5 zeolite with high silica-alumina ratio at 350oC. It therefore follows that zeolite canfunction as a catalyst in aldol type condensation reactions and that weak acid sites as well as a small number of active sites favor the aldolcondensation reaction of carbonyl compounds. However, the mixed condensation product was found to be favored at temperatures above 300oCand the self-condensation of ethanal to crotonaldehyde was favored at temperatures below 300oC. It has also been suggested that both Brønstedand Lewis acids are involved in aldol reactions with Lewis acid sites the most probable catalytic sites. The zeolite group of minerals has founduse in many chemical and allied industries. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.12291 Int J Appl Sci Biotechnol, Vol. 3(1): 1-8